Prevalence of obesity and disturbances in glucose homeostasis in HIV‐infected subjects and general population – missed diagnoses of diabetes?. Issue 4 (9th November 2020) - Hanttu, A; Kauppinen, KJ; Kivelä, P; Ollgren, J; Jousilahti, P; Liitsola, K; Koponen, P; Sutinen, J
Abstract : Objectives: Comparative data on glucose disorders using fasting blood samples between people living with HIV (PLWH) and the general population are lacking. The objective of this study was to compare the prevalence and risk factors of obesity and disturbances in glucose homeostasis between PLWH treated with modern antiretroviral therapy and the general population. Methods: Adjusted prevalence of obesity, features of insulin resistance (triglyceride:high‐density lipoprotein cholesterol ratio and alanine aminotransferase), impaired fasting glucose (IFG), diabetes mellitus (DM) and combined dysglycaemia (presence of IFG or DM) were determined using fasting blood samples among 1041 PLWH and 7047 subjects representing the general population. Results: People living with HIV had a lower prevalence of obesity [18.2%, 95% confidence interval (CI): 15.1–21.2 vs . 23.9%, 95% CI: 22.4–25.4], but a higher prevalence of insulin resistance and IFG (20.0%, 95% CI: 16.6–23.4 vs . 9.8%, 95% CI: 8.7–10.8) than the general population. Fasting glucose concentration was higher, but glycated haemoglobin (HbA1c) was lower, among PLWH. Prevalence of dysglycaemia for a given body mass index (BMI) was higher in PLWH than in the general population. The prevalence of DM did not differ between PLWH (13.2%, 95% CI: 10.2–15.9) and the general population (14.5%, 95% CI: 13.6–15.4). Conclusions: The prevalence of obesity was lower, but the risk of dysglycaemia for a given BMI was significantly higher, among PLWH, highlighting the importance of prevention and treatment of obesity among HIV‐infected subjects. Regardless of the increased prevalence of insulin resistance and IFG, DM was surprisingly not more common among PLWH, raising concern about the under‐diagnosis of DM, possibly due to low sensitivity of HbA1c in this patient population.